School culture, teacher professionality and student achievements of state elementary school 01 Banyubiru (an ethnographic review) - Toni Heriyanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
The general objectives of this study were to identify various problems related to school culture and teacher professionalism at SD Negeri Banyubiru 01, identify various obstacles and strategies for implementing school culture and teacher professionalism at SD Negeri Banyubiru 01, and determine how school culture and teacher professionalism affect student performance. This study used an ethnographic design and combined ethnographic procedures. This study included many respondents, including teachers, school administrators, staff, students, and others, who were selected using a purposive sampling method. Data collection methods included observation, focus group discussions, documentation, and interviews. Data were validated using member verification and triangulation techniques. Data analysis was conducted using the Creswell data model. The school day at SD Negeri Banyubiru 01 showed that the school day affected school spirit. Some school activities included socialization in class, teamwork and dhuha prayer, and religious education. The two main factors that hinder teacher professional development are cost and time. Teachers must set aside funds for students to participate in classes or programs and time to learn and improve their skills. In addition, a teacher may be able to explain the changes and difficulties in implementing new practices. It can be challenging to carry out professional development activities. Sometimes, teachers cannot fully use the knowledge and skills they have to teach students in everyday life